Determination of Amount of Allowable DERs by Analyzing Voltage Variations with Physical Distribution System Model - Baek, Seung-Mook (International Journal of Advanced Science and Technology, 2020)
The paper describes a method to determine an amount of allowable distributed energy resources (DERs) by analyzing voltage variations with a physical distribution system model. As the penetration of DERs in the distribution system becomes high, the power system has faced new problems such as voltage variations, protection fail, and reverse power flow. Also, the high penetration of DERs can cause frequent changes in the direction of the power flow and hence the system voltages vary over a wider range. In the paper, distribution system in South Korea is modeled and the problems caused by the high penetration of DERs are investigated. Especially, the paper presents important technical requirements and ways to apply those requirements to determine the allowable DERs.